2018
DOI: 10.1038/s41586-018-0157-4
|View full text |Cite
|
Sign up to set email alerts
|

Reconstruction of antibody dynamics and infection histories to evaluate dengue risk

Abstract: As with many pathogens, most dengue infections are subclinical and therefore unobserved1. Coupled with limited understanding of the dynamical behavior of potential serological markers of infection, this observational problem has wide-ranging implications, including hampering our understanding of individual- and population-level correlates of infection and disease risk and how they change over time, assay interpretation and cohort design. We develop a framework that simultaneously characterizes antibody dynamic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

18
290
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 243 publications
(309 citation statements)
references
References 38 publications
18
290
1
Order By: Relevance
“…Vaccines for ZIKV are under development, but the path to approval may be exceedingly difficult because of antibody cross-reactivity with other flaviviruses and the possibility of disease enhancement (Bardina et al, 2017; George et al, 2017; Halstead, 2018; Harrison, 2016; Heinz and Stiasny, 2017; Katzelnick et al, 2017; Salje et al, 2018; Stettler et al, 2016). Passive administration of monoclonal antibodies represents an alternative approach to vaccines because human monoclonal antibodies can effectively neutralize the virus in vitro and protect against ZIKV infection in mice (Fernandez et al, 2017; Robbiani et al, 2017; Sapparapu et al, 2016; Stettler et al, 2016; Swanstrom et al, 2016; Yu et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…Vaccines for ZIKV are under development, but the path to approval may be exceedingly difficult because of antibody cross-reactivity with other flaviviruses and the possibility of disease enhancement (Bardina et al, 2017; George et al, 2017; Halstead, 2018; Harrison, 2016; Heinz and Stiasny, 2017; Katzelnick et al, 2017; Salje et al, 2018; Stettler et al, 2016). Passive administration of monoclonal antibodies represents an alternative approach to vaccines because human monoclonal antibodies can effectively neutralize the virus in vitro and protect against ZIKV infection in mice (Fernandez et al, 2017; Robbiani et al, 2017; Sapparapu et al, 2016; Stettler et al, 2016; Swanstrom et al, 2016; Yu et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…In vitro, antibodies can mediate ADE of infection in cells expressing Fc gamma receptor (FcγR) at sub-neutralizing concentrations (Pierson et al, 2007). Recent studies in humans have also demonstrated that the risk of severe dengue disease following secondary infection is greatest within a range of intermediate titers of pre-existing DENV-specific antibodies, while higher titers are protective against symptomatic infection (Katzelnick et al, 2017;Salje et al, 2018). Thus, eliciting potently neutralizing antibodies is desirable to limit the concentration range within which ADE can occur.…”
Section: Ade Potential Of Mabsmentioning
confidence: 99%
“…Approximately 20% of DENV-infected individuals develop a mild febrile illness, of which 5% to 20% progress to potentially fatal severe disease, characterized by bleeding, plasma leakage, shock, and organ failure (Guzman & Harris, 2015;Khursheed et al, 2013;Thein, Leo, Lee, Sun, & Lye, 2011). Epidemiological studies have shown that pre-existing antibodies from a primary DENV infection are a risk factor for severe disease following subsequent infection with a heterologous DENV serotype (Katzelnick et al, 2017;Salje et al, 2018;Sangkawibha et al, 1984). This is partly attributed to the prevalence of cross-reactive antibodies from the initial infection that can bind, but not neutralize the secondary heterologous virus.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Subsequent heterotypic secondary infection induces broad cross-protection, and symptomatic tertiary and quaternary cases are rare (Gibbons et al, 2007;Olkowski et al, 2013). However, a small subset of secondary infections are enhanced by non-neutralizing, cross-reactive antibodies, resulting in severe disease via antibody dependent enhancement (ADE) (Halstead, 1979;Katzelnick et al, 2017;Salje et al, 2018;Sangkawibha et al, 1984). Approximately 1-3% of cases progress to severe dengue hemorrhagic fever, causing ∼9,000 deaths each year (Bhatt et al, 2013;Stanaway et al, 2016) and relative risk of severe dengue from secondary heterotypic infection relative to primary infection is estimated to be ∼24 (Mizumoto et al, 2014).…”
Section: Introductionmentioning
confidence: 99%